2021
DOI: 10.1109/jsen.2020.2989202
|View full text |Cite
|
Sign up to set email alerts
|

Surge Compression for Improved Fault Location Accuracy in Full Transient-Based Methods

Abstract: This paper proves that the accuracy of singleended fault location techniques based on the correlation of fault transients in power lines can be significantly improved by inversefiltering transients first. The reason for this improved accuracy is found in the reduction of the duration of the fault surge signal, thus increasing the sensitivity of fault-location metrics to the fault position. Reported results show that by using the proposed filtering strategy, faster sampling rates systematically and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This metric takes into account that the signal energy might notably reduce when the back-injected transients propagate through line junctions (this issue was also observed by Razzaghi et al in their first publications). In 2021, Cozza et al (2021b) proposed an inverse filtering surge compression method, which was shown to be capable of using a relatively low sampling rate (can be as low as 100 ksps) to estimate the transfer functions from fault transient signals. Besides, He et al (2020b) discussed the spatial resolution of the correlation metric, which was defined using the theory of Fabry-Pérot interferometers as the minimum shift from the true fault location to an adjacent guessed fault location induced by the minimum variation between their corresponding resonance frequencies.…”
Section: Focusing/location Metricsmentioning
confidence: 99%
“…This metric takes into account that the signal energy might notably reduce when the back-injected transients propagate through line junctions (this issue was also observed by Razzaghi et al in their first publications). In 2021, Cozza et al (2021b) proposed an inverse filtering surge compression method, which was shown to be capable of using a relatively low sampling rate (can be as low as 100 ksps) to estimate the transfer functions from fault transient signals. Besides, He et al (2020b) discussed the spatial resolution of the correlation metric, which was defined using the theory of Fabry-Pérot interferometers as the minimum shift from the true fault location to an adjacent guessed fault location induced by the minimum variation between their corresponding resonance frequencies.…”
Section: Focusing/location Metricsmentioning
confidence: 99%
“…Since then, some scholars have begun to study multiple information fusion methods, such as analyzing the corresponding relationship between specific communication links and secondary devices based on network partitioning and extracting some key messages to identify the operation of relay protection secondary circuits [4] . This method adds message information from other secondary devices based on fault secondary device self-inspection information, thereby improving the accuracy of secondary device fault location.…”
Section: Introductionmentioning
confidence: 99%
“…The time-reversal (TR) method refers to when the response signal of a system is turned into a reversal signal and then input into the system, and the original waveform is reconstructed at the initial position. [1,2] TR has the characteristics of spatiotemporal focusing, which can be used in various fields such as pulse compression, [3][4][5] secret communication, [6,7] reversal imaging, [8,9] beam forming, [10][11][12][13] positioning, [14,15] perturbation detection, [16,17] etc. The first electromagnetic reversal system consisted of a single transmitting and receiving antenna and a reverberation chamber with a high Q value.…”
Section: Introductionmentioning
confidence: 99%